2023
DOI: 10.3389/fphys.2023.1106474
|View full text |Cite
|
Sign up to set email alerts
|

Prx1 cell subpopulations identified in various tissues with diverse quiescence and activation ability following fracture and BMP2 stimulation

Abstract: The expression of Prx1 has been used as a marker to define the skeletal stem cells (SSCs) populations found within the bone marrow and periosteum that contribute to bone regeneration. However, Prx1 expressing SSCs (Prx1-SSCs) are not restricted to the bone compartments, but are also located within the muscle and able to contribute to ectopic bone formation. Little is known however, about the mechanism(s) regulating Prx1-SSCs that reside in muscle and how they participate in bone regeneration. This study compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Examination of 2.4-kb prx1 limb-specific enhancer activity showed that it is strongly activated in mononuclear cells under the wound epidermis in Xenopus froglets but not in mouse skin [2]. Nevertheless, the activity of prx1 in mice is crucial for skeletal stem cell populations found within the bone marrow, periosteum and muscles that contribute to bone regeneration [14].…”
Section: Introductionmentioning
confidence: 99%
“…Examination of 2.4-kb prx1 limb-specific enhancer activity showed that it is strongly activated in mononuclear cells under the wound epidermis in Xenopus froglets but not in mouse skin [2]. Nevertheless, the activity of prx1 in mice is crucial for skeletal stem cell populations found within the bone marrow, periosteum and muscles that contribute to bone regeneration [14].…”
Section: Introductionmentioning
confidence: 99%